Leadership Crisis in Nepali Politics: Specific Focus on National Parties in the Context of Declaration of the Republic - Devkota, Khimlal (Social Inquiry: Journal of Social Science Research, 2019)
The article reflects upon different political movements that took place in Nepal before Nepal was declared a republic and argues that all the earlier political movements failed to declaration of republic, because of the crisis of leadership and leaders’ dilemma to make decisions in the right time. The article is prepared based on the survey of literature on Nepali political transition ranging from the Rana regime, a close study of Nepali politics till the declaration of republic in 2008 mapping of literature related with leadership skills and qualities. After a comprehensive study, I have come to a conclusion that Nepali political movements have repeatedly failed due to the failure and crisis of leadership because of indecisiveness. Right decision in right time is make sense of leadership quality.